Penatalaksanaan Fisioterapi Pada Osteoarthritis Lutut Dextra Di Rst Magelang - Wahid, Ahmad, Dwi Kurniawati, SSt..FT, M.Kes (2015)
Background: Knee Osteoarthritis is a degenerative joint disease Dextra in the form of joint cartilage dam age that developed slowly, no known cause disease had Dampen the joints most often found than the other joint disease.Objective: To investigate the implementation of physiotherapy in reducing pain, increasing range of motion and increase muscle strength in the case of Knee Osteoarthritis Dextra using modalities Infra Red (IR) danTerapi exercise (TL). Results: After treatment for 6 times can result in pain assessment on pain silent T1: 1 to T6: 1, nyeritekan T1: 4 to T6: 2, nyerigerak T1: 4 to T6: 3, incr eased range of motion S: T1: S 0 -0 -125 become T6: S 0-0 -135, increase muscle strength right knee hip flexors T1: 4-become T6: 4+, hip ektensor T1: 4-be T6: 4+. Conclusion: Micro Wave Diameter (MWD) can reduce pain in the right knee on the Knee Osteoar thritis Dextra case, exercise therapy (TL) can increase the range of motion in the right knee Knee Osteoarthritis Dextra case and can improve muscle strength in Knee Osteoarthritis Dextra case.